Government for the future unification, fragmentation, and regionalism - Andersson, ôke E., 1936-; Hårsman, Björn; Quigley, John M., 1942- (Elsevier, 1997)
The aim of this volume is to encourage comparative explorations of the links between economic regionalism and government behaviour. At present, the relation between government and the economy is in a state of flux. In the old developed world, supranational organizations such as the EU and the WTO, are exerting more influence over economic life. Simultaneously, regional governments have emerged to provide public services to local populations. In some European countries, economic decision making is no longer in the power of the nation state, but has been transfered to international and local organizations. The papers in this volume have been contributed by a broad range of policy makers, journalists, and academics. Theories of the public sector are reviewed, restructured and extended, in order to cover the new spatial and dynamic situation. The volume provides historical and institutional perspectives on the public sector, and presents empirical case studies of the public sectors in Sweden, USA, Belgium, Malaysia, England and Singapore.
Papers from a series of conferences held since 1991, organized by the Institute for Futures Studies in Stockholm.
Keywords: Central-local government relations -- Congresses.; Decentralization in government -- Congresses.; Federal government -- Congresses.; Economic policy -- Congresses.; Political Science -- Government -- State & Provincial.; Business & Economics -- Economics -- Macroeconomics.; Political economy.; Public finance.; elektronické knihy; electronic books